2015
DOI: 10.1051/0004-6361/201425543
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the Janus-Epimetheus system through collisions

Abstract: Context. Co-orbital systems are bodies that share the same mean orbit. They can be divided into different families according to the relative mass of the co-orbital partners and the particularities of their movement. Janus and Epimetheus are unique in that they are the only known co-orbital pair of comparable masses and thus the only known system in mutual horseshoe orbit. Aims. We aim to establish whether the Janus-Epimetheus system might have formed by disruption of an object in the current orbit of Epimetheu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In light of the Janus/Epimetheus formation model proposed in Treffenstädt et al (2015), we envision the following scenario for the formation of a 1+𝑁 co-orbital satellite system (Figure 13): Initially, we assume an ancient system composed of the moon 𝑆 1 (𝑅 S 1 = 5.2 km) and an object located at one of its triangular points (trojan). After an impact with an ongoing object (Figure 13a), the trojan disrupts, forming a set of fragments (Figure 13b).…”
Section: Impact Between An Ongoing Object and A Trojan Moonmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of the Janus/Epimetheus formation model proposed in Treffenstädt et al (2015), we envision the following scenario for the formation of a 1+𝑁 co-orbital satellite system (Figure 13): Initially, we assume an ancient system composed of the moon 𝑆 1 (𝑅 S 1 = 5.2 km) and an object located at one of its triangular points (trojan). After an impact with an ongoing object (Figure 13a), the trojan disrupts, forming a set of fragments (Figure 13b).…”
Section: Impact Between An Ongoing Object and A Trojan Moonmentioning
confidence: 99%
“…We evaluate the effects of Galatea in the co-orbital system and also propose different scenarios for the formation of the arcs. Treffenstädt et al (2015) showed that the collisions of large fragments produced in the disruption of an ancient satellite might form Janus and Epimetheus. Following this work, we suggest the formation of co-orbital satellites through the disruption of an ancient body located at a triangular point of a satellite.…”
Section: Introductionmentioning
confidence: 99%
“…Embedded within several of the main rings are a series of small moonlets (Tiscareno et al 2006) and several shepherd satellites (Showalter 1991;Porco et al 2007;Cuzzi et al 2014). The co-orbitals Janus and Epimetheus (Yoder et al 1983(Yoder et al , 1989Nicholson et al 1992;Treffenstädt et al 2015;El Moutamid et al 2016), and their associated faint ring system (Winter et al 2016) are unique to the Saturn system. Just beyond the Janus/Epimetheus orbit, there is a diffuse G-ring, the source of which is the satellite Aegaeon (Hedman et al 2007a).…”
Section: The Saturnian Systemmentioning
confidence: 99%
“…As these bodies were being discovered, many important works were made to study the co-orbital systems. There are studies on the dynamics in a restricted three-body problem (Danby 1964;Dermott & Murray 1981a;Lohinger & Dvorak 1993;Mittal et al 2020), on the stable regions around Lagrangian points (Deprit & Deprit-Bartholomé 1967;Marchal 1991;Érdi & Sándor 2005;Érdi et al 2007;Zhou et al 2009;Ćuk et al 2012), studies on the co-orbital regions of Solar System's planets (Mikkola & Innanen 1992;Nesvornỳ & Dones 2002;Scholl et al 2005;Tabachnik & Evans 2000), dynamics of some known co-orbital satellites (Dermott & Murray 1981b;Yoder et al 1983;Treffenstädt et al 2015), on stability and formation of the Solar System's trojans (Izidoro et al 2010;Donnison & Williams 1985;Chanut et al 2008;Mourão et al 2006;Pitjeva & Pitjev 2019;Zhou et al 2011Zhou et al , 2019Zhou et al , 2020Dvorak, R. et al 2012;Mikkola & Innanen 1990;Lykawka et al 2009Lykawka et al , 2011Marzari & Scholl 2013), and even hypothetical coorbital exoplanets (Schwarz et al 2009(Schwarz et al , 2012(Schwarz et al , 2015Beaugé et al 2007;.…”
Section: Introductionmentioning
confidence: 99%